SWOT Analysis as a Strategy for Enhancing the Competitiveness of Creative Industry MSMEs at Snapbox Studios - Dwi Afifah Nurzahra; Siti Isma Maysaroh; Fadhilah Aditya Akbar; Hoang Le Thuy Linh; 謝昕頤 謝昕頤; 施宣妤; 陳姵妍 陳姵妍; 陳璦捷 (Oikonomia : Journal of Management Economics and Accounting, 2026)
The creative industry, particularly self-photo studios, is growing rapidly along with the changing behavior of Generation Z consumers who prioritize experiences and social media content. However, creative SMEs like Snapbox Studios face challenges in maintaining competitiveness due to intense competition and operational limitations. This study aims to analyze internal factors (strengths and weaknesses) as well as external factors (opportunities and threats) faced by Snapbox Studios, and to formulate competitive strategies based on SWOT analysis. The method used is a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews with the owner, direct observation, and documentation. The research results identify that the main strengths of Snapbox Studios lie in its unique vintage concept, affordable prices, strategic location, and proactive promotion through social media and KOL collaborations. The weaknesses identified include frequent hardware malfunctions, limited session capacity, suboptimal additional products, and the absence of a digital payment system and loyalty program. Opportunities that can be leveraged include activity-based experience trends, the popularity of short video content, and the increasing adoption of digital payments. The main threats come from four direct competitors, changes in social media algorithms, and low customer loyalty. Based on the SWOT matrix, four strategies are formulated: SO (aggressive), WO (turnaround), ST (diversification), and WT (defensive). The recommended top priorities are the integration of digital payments, routine hardware maintenance, optimization of additional products, and the development of a digital loyalty program. In conclusion, Snapbox Studios has the potential to grow by implementing strategies focused on service digitalization, operational improvements, and revenue diversification